7Be atmospheric activity concentration and meteorological data: Statistical analysis and two-layer atmospheric model - Uhlář, R; Haroková, P; Alexa, P; Kačmařík, M (Journal of environmental radioactivity, 2020)
Atmospheric activity concentration of 7Be in the air was monitored during the period of one year from September 2015 to September 2016 at Ostrava, Czech Republic, with a two-day frequency that is shorter compared to a standard 7-day frequency of routine 7Be measurements. Simultaneously, relevant meteorological data (temperature, rainfall amount, precipitation particle size and speed, tropopause height, and PM10 concentrations) and the sunspot number were accumulated. Weighted linear regression analysis applied to the 7Be atmospheric activity concentration, the measured meteorological explanatory variables and the sunspot number revealed temperature as the most statistically significant explanatory variable. The tree model proved temperature as the most important explanatory variable and predicted the threshold value separating low and high temperature behavior of 7Be at about 13 °C (2-day average). A simple local two-layer (stratosphere and troposphere) atmospheric model was then applied to the data analysis. The model is able to fit the data for a larger accumulation period (6 days).
Keywords: Seasons; monitorování životního prostředí; látky znečišťující vzduch; Air Pollutants; Time Factors; radionuklidy; Česká republika; Environmental Monitoring; Radioisotopes; Czech Republic; Radiation Monitoring; beryllium; velikost částic; monitorování radiace; Beryllium; Temperature; časové faktory; roční období; Particle Size; teplota